2018
DOI: 10.5603/kp.a2018.0089
|View full text |Cite|
|
Sign up to set email alerts
|

Lead-related complications after DDD pacemaker implantation

Abstract: Leads with polyurethane 80A insulation, unipolar construction, and those implanted via subclavian vein puncture exhibited the worst long-term performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The survival and lead -related complications in the present cohort have been studied previously. 9,14,15 The endpoints were the onset of permanent AF and all--cause mortality. The data used in the analysis included 1) patients' demographic baseline characteristics: age at implantation and sex; 2) index arrhythmia (primary electrocardiographic pacing indication): atrioventricular block (AVB) or sick sinus syndrome (SSS); 3) a history of AF prior to DDD PPM implantation; 4) position of the RV lead: apical or nonapical at discharge from the department; 5) time of permanent AF onset; and 6) date of death declared in the death certificate.…”
mentioning
confidence: 99%
“…The survival and lead -related complications in the present cohort have been studied previously. 9,14,15 The endpoints were the onset of permanent AF and all--cause mortality. The data used in the analysis included 1) patients' demographic baseline characteristics: age at implantation and sex; 2) index arrhythmia (primary electrocardiographic pacing indication): atrioventricular block (AVB) or sick sinus syndrome (SSS); 3) a history of AF prior to DDD PPM implantation; 4) position of the RV lead: apical or nonapical at discharge from the department; 5) time of permanent AF onset; and 6) date of death declared in the death certificate.…”
mentioning
confidence: 99%
“…Increasing use of CIEDs is associated with increased complications, including lead dislodgements. Recently, numerous studies have evaluated the risk factors of lead dislodgements [ 6 , 13 , 17 , 18 ]. For instance, Dębski et al [ 17 ] showed that atrial lead position is an independent risk factor of lead dislodgement.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Dębski et al [4] is a timely article which discusses the issue of lead longevity. The authors should be congratulated for their work.…”
Section: Lead Failurementioning
confidence: 99%
“…In the near-term time horizon, we will likely use single chamber VDD and multicomponent dual chamber leadless pacemakers, as well as those which communicate with the subcutaneous implantable cardioverter-defibrillator [12]. Studies like this one from Dębski et al [4] on transvenous pacemaker leads will hopefully be less needed. Leads continue to be the "weakest link" in the chain of cardiac pacing [13] but it appears that we are at the brink of the much-needed next revolution in cardiac pacing -a world without leads!…”
Section: Lead Failurementioning
confidence: 99%